Role of ecosystem services in private lands conservation: an investor's perspective - Anderson, Terry, speaker; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
The concept of ecosystem services has evolved from society's earliest basic needs of obtaining food and shelter to today's complex ecological paradigms that include social, cultural, and economic and conservation objectives. While scientists and environmentalists have discussed ecosystem services implicitly for decades, the current nomenclature began to refine significantly in the1990s and 2000s. Correspondingly, during this same period, the idea of private sector/investment driven/conservation finance began to take form in an arena long dominated by public finance and philanthropy. Thus, the opportunity of the day: How do we better define effective formulas that match ecological opportunity with available private capital? Refining, or in many cases, developing the value chain between the worlds of conservation and financial investment is a major part of the solution. Financial advisors and investors must become as comfortable evaluating ecosystem services, like aquifer recharge and water quality credits, as with evaluating commodity pricing for minerals or agricultural products. Equally, the conservation world will improve its track record greatly by learning to conduct rigorous project diligence and selection processes similar to those applied in more traditional investment contexts. While, significant progress has occurred, particularly in the more advanced markets of wetland, stream or species banking, there remains the challenge of effectively leveraging these early gains into the numerous larger, yet less developed, ecosystem markets.
Role of ecosystem services in private lands conservations: an investor's perspective
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses